Intergrasi Konteks Kehidupan Nyata dalam Pengembangan Bahan Ajar Audio untuk Maharah Istima' - Sayyidaturrohimah, Sayyidaturrohimah (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2024)
Teaching materials are a crucial component in the learning process. Their availability can significantly impact the achievement of learning objectives and students' understanding of the material. This study aims to develop audio teaching materials based on a contextual approach for maharah istima’ expecially at MTsN 6 Ponorogo, as well as to describe how the integration of the contextual approach is implemented in the developed teaching materials. The research method used is a research and development method following the Borg and Gall development model. The data collection techniques employed include interviews, observations, questionnaires, and documentation. The data analysis techniques used are Milles and Huberman's qualitative data analysis and descriptive quantitative data analysis. The results indicate that the development of teaching materials in this study is based on four student needs related to Arabic language learning. These four needs have been realized into audio-based teaching materials, complemented by a workbook to support maharah istima’ learning. Furthermore, aspects of real-life context in these teaching materials are integrated into four areas: media that align with the current context of technological development, materials and exercises that relate to students' real-life contexts, and learning activities that align with the seven principles of the contextual approach.